Criminal penalties for individuals who create stickers with other people's faces - Kurniawan, Danang Arif (Gema Wiralodra, 2024)
The crime category is people who edit stickers with other people's faces that are distributed via online media. This study uses a legal-normative research method. Data was collected using a literature study on related legal materials and analyzed descriptively. The research results are based on the Information and Electronic Transactions Law (UU ITE) and the Copyright Law. ITE Law Article 32 Paragraph (1) Article 32 Paragraph (1) of the ITE Law states that making WhatsApp stickers with a person's face without permission, which can insult, harass, or harm the individual's reputation, can be considered a violation of this article. Violations of this article may be subject to criminal penalties and/or fines under the provisions of the ITE Law Article 48 Paragraph (1). Article 48 Paragraph (1) regulates criminal sanctions for violations included in the offense of complaints. If proven to violate and offend the person in the photo, they can be subject to sanctions under the ITE Law, according to Article 27 paragraph (3) of the ITE Law, namely under Article 45 paragraph (1) The ITE Law, which states that you can be punished with imprisonment for a maximum of 6 (six) years and/or a fine of a maximum of IDR 1,000,000,000. Implications include increased scrutiny of digital content and potential policy revisions to strengthen legal protections for individuals who are victims of unauthorized use of their faces.